2018
DOI: 10.5812/zjrms.63006
|View full text |Cite
|
Sign up to set email alerts
|

The Main Causes of Mortality in Pediatric Intensive Care Unit in South West of Iran

Abstract: Background: The decreasing of mortality rate is one of the most important goals in every intensive care unit (ICU). This study was performed to determine the main causes of admission and mortality rate in our referral pediatric ICU (PICU). Methods: In this retrospective study, all patients (age-group, 1 month-16 years) admitted to the PICU in one year were included and patients with less than a 3h duration of admission, multiple traumas, and post-surgery patients were excluded. Results: Among the 688 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 13 publications
6
18
3
Order By: Relevance
“…e majority of patients at the SUH PICU were infants who also constituted the highest age-related mortality. is was also reported in different studies performed in many developing countries with higher population of children [17,18]. is confirms the need to direct more resources to reduce the in-hospital mortality of this vulnerable age group.…”
Section: Discussionsupporting
confidence: 69%
“…e majority of patients at the SUH PICU were infants who also constituted the highest age-related mortality. is was also reported in different studies performed in many developing countries with higher population of children [17,18]. is confirms the need to direct more resources to reduce the in-hospital mortality of this vulnerable age group.…”
Section: Discussionsupporting
confidence: 69%
“…The level of GCS of <8 has a factor in the mortality of PICU in our review. This finding is supported by studies conducted in Iran (30) and the Netherlands (31). The possible explanation for this factor was that decreased GCS level results in more critical patients and increased mortality.…”
Section: Discussionsupporting
confidence: 79%
“…This result is analogous to research from Jimma, Ethiopia, which reported a high mortality rate in patients who stayed for more than 28 days 13 and Iran, which discovered a 2.49 times higher mortality rate in patients who stayed for longer than a week. 34 Our findings may be explained by the fact that patients who stay in the hospital for a long time are more likely to develop hospital-acquired infections.…”
Section: Discussionmentioning
confidence: 74%